Costs of Sovereign Defaults : Restructuring Strategies, Bank Distress and the Capital Inflow-Credit Channel - Asonuma, Tamon; Chamon, Marcos; Erce, Aitor; Sasahara, Akira (Washington, D.C. : International Monetary Fund, 2019)
Sovereign debt restructurings are associated with declines in GDP, investment, bank credit, and capital flows. The transmission channels and associated output and banking sector costs depend on whether the restructuring takes place preemptively, without missing payments to creditors, or whether it takes place after a default has occurred. Post-default restructurings are associated with larger declines in bank credit, an increase in lending interest rates, and a higher likelihood of triggering a banking crisis than pre-emptive restructurings. Our local projection estimates show large declines in GDP, investment, and credit amplified by severe sudden stops and transmitted through a 'capital inflow-credit channel'.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet